Analisis Nilai Karakter Pada Cerpen “Pohon Keramat” Karya Yus R. Ismail - Siti Suryani; Winda Siti Nabila (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Literary works are depictions of the reality of life which are used as tools to express imagination and thoughts around them. In this research, the author aims to reveal the character values ​​contained in the short story entitled